Assessing apical transportation in curved canals: comparison between cross-sections and micro-computed tomography - Laila Gonzales Freire; Giulio Gavini; Rodrigo Sanches Cunha; Marcelo dos Santos (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The aim of this study was to compare two methods of assessing apical transportation in curved canals after rotary instrumentation, namely, cross-sections and micro-computed tomography (µCT). Thirty mandibular molars were divided into two groups and prepared according to the requirements of each method. In G1 (cross-sections), teeth were embedded in resin blocks and sectioned at 2.0, 3.5, and 5.0 mm from the anatomic apex. Pre- and postoperative sections were photographed and analyzed. In G2 (µCT), teeth were embedded in a rubber-base impression material and scanned before and after instrumentation. Mesiobuccal canals were instrumented with the Twisted File (TF) system (SybronEndo, Orange, USA), and mesiolingual canals, with the EndoSequence (ES) system (Brasseler, Savannah, USA). Images were reconstructed, and sections corresponding to distances 2.0, 3.5, and 5.0 mm from the anatomic apex were selected for comparison. Data were analyzed using Mann-Whitney's test at a 5% significance level. The TF and ES instruments produced little deviation from the root canal center, with no statistical difference between them (P > 0.05). The canal transportation results were significantly lower (0.056 mm) in G2 than in G1 (0.089 mm) (p = 0.0012). The µCT method was superior to the cross-section method, especially in view of its ability to preserve specimens and provide results that are more closely related to clinical situations.